(untitled) - Netzley, Patricia D. (San Diego, 2003)
Between 10,000 and 25,000 Apache lived in the American Southwest in the mid-19th century. This book tells about the lifestyle of an Apache warrior during this time, providing details about housing, clothing, hunting practices, tools, weapons, and other important aspects of Apache society.
Keywords: Apache Indians,Apache Indians; Warfare,Văn học vị thành niên; Người Apache